The Role of the Sabhara Patrol Unit in Preventing Illegal Racing Actions in the Barelang Police Area - Ilham Anggara (Police Studies Review, 2021)
The rise of illegal racing actions that occurred resulted in Kamtibmas in Batam City being not conducive. The increase in the intensity of the illegal racing action that occurs is very disturbing for the residents of Batam City in carrying out their daily activities. Teenagers are the dominant group as perpetrators of illegal racing. Thus forcing the Barelang Police, namely the Sabhara unit, to work hard in preventing illegal racing actions that are troubling the people of Batam City. The purpose of the research in this thesis is to describe the description of the patrols of the Barelang Police Sabhara Unit and the description of illegal racing in Batam City, to describe the role of patrols in preventing illegal racing in the Barelang Police jurisdiction, to find the factors that influence the implementation of patrols in preventing illegal racing. This study uses qualitative methods, while the theories and concepts used to analyze this problem are Role Theory, Management Theory, Crime Prevention Theory, Patrol Concepts, Crime Prevention Concepts, Illegal Racing Violation Concepts.Data collection techniques that can be used are interviews, observation, and document studies. The results obtained in this study are the role of the Sabhara Polresta Barelang patrol unit is to maintain security and public order is good, but the role of enforcing the law, and the role of providing protection, shelter and service to the community is not good. In the implementation of patrols, there are several factors, including supporting and inhibiting factors. Suggestions for the Sabhara Polresta Barelang unit to improve the ability of patrol members by participating in Sabhara function ability training, the need for additional 2-wheel patrols at night regularly, giving awards to patrol officers who carry out their duties and responsibilities well, providing a forum for teenagers to can channel their interests and talents to do wild racing, and it is necessary to have a varied time for the implementation of patrols.